2000
DOI: 10.1097/00000478-200012000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma With Paradoxical Maturation

Abstract: Typically, melanocytic nevi "mature" (i.e., exhibit a morphologic shift to smaller or spindle cells with progressive depth in the dermis). In contrast, most malignant melanomas (conventional MMs) lack maturation, and are composed of large pleomorphic cells throughout. The authors describe a series of melanomas with paradoxical maturation mimicking the pattern of nevi. Seventeen primary invasive melanomas with paradoxical maturation (IMPs), two epidermotropic metastatic melanomas with maturation (EMMMs), 13 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 26 publications
6
31
0
1
Order By: Relevance
“…1,6 In contrast, most melanomas lack maturation but exhibit relatively uniform cytology in both superficial and deep components. They also demonstrate large, hyperchromatic nuclei with irregular nuclear membranes and prominent nucleoli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,6 In contrast, most melanomas lack maturation but exhibit relatively uniform cytology in both superficial and deep components. They also demonstrate large, hyperchromatic nuclei with irregular nuclear membranes and prominent nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrate large, hyperchromatic nuclei with irregular nuclear membranes and prominent nucleoli. 1 The histologic findings of a large series of nonsurgically traumatized nevi have been previously described, but the kinds of trauma were not elucidated. 7 Trau et al 8 observed that recurrent lesions after laser therapy often have superficial similarities with melanoma, both clinically and histologically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter, the deepest portion of the melanoma can show diminution in the size of nests and individual cells, thereby mimicking the pattern of a benign nevus. 8 We have shown earlier that a fluorescence in situ hybridization (FISH) assay targeting 6p25 (RREB1), 6q23 (MYB), 11q13 (CCND1) and CEP6 could distinguish benign and malignant melanocytic neoplasms with high sensitivity and specificity. 9 In this study, we evaluated 36 melanomas with associated nevi and 6 nevoid melanomas with deep dermal involvement using FISH with probes targeting 6p25, 6q23, CEP6 and 11q13.…”
mentioning
confidence: 99%
“…Histologic maturation is described as a morphologic change of large and epithelioid type A nevomelanocytes to smaller and spindle-shaped type C nevomelanocytes with progressive descent into the dermis. 1,2 Conventional malignant melanomas display similar cytology in both their superficial and deep portions (this is not the case with melanomas that paradoxically do not exhibit such maturation; see below). 2 This lack of maturation provides a useful visual clue to the correct diagnosis of melanoma.…”
Section: Introductionmentioning
confidence: 99%